An Econometric Analysis of Causal Relationship Between Gold, Crude Oil, U.S. Dollar Rates and S&P BSE 100 in India - Jothi, M.; Suresh, G. (Indian Journal of Research in Capital Markets, 2016)
In the present day globalized business scenario, volatility in gold prices, international crude oil prices, and U.S. Dollar exchange rate is likely to stimulate uncertainty in the stock market conditions globally. The degree of uncertainty in the stock market is high in the case of developing nations like India. Therefore, the study of causal relationship of gold, crude oil, and U.S. Dollar rates with the stock market indices (S & P BSE 100) in India is more appropriate. We analyzed these macro economic variables along with the S&P BSE 100 with the help of econometric tools - Augmented Dickey-Fuller Test for unit-root, Johansen co-integration test, pairwise Granger causality tests, vector auto regression modeling, variance decomposition test, and impulse response analysis. The econometric research software called EVIEWS 6 was used to apply all these tools successfully. The results showed that there was a high impression in the Indian stock market due to the volatility that happens in the described macro-economic factors.